أثر العائلة في تفعيل دور المسير في المؤسسات الصغيرة والمتوسطة دراسة حالة عينة من المؤسسات - مرزوقي, مرزوقي (University of Ouargla جامعة ورقلة, 2016)
باتت المؤسسات الصغيرة والمتوسطة اليوم تشكل جانبا مهما في الاقتصاديات المتقدمة والنامية على السواء، وعليه أصبح لزاما على مسيري المؤسسات الصغيرة والمتوسطة أن يدركوا أن التفوق التنافسي أساسه الابتكار سواء على المستوى المحلي أو العالمي وهو العامل الأكثر أهمية في التحول من مرحلة الحماية إلى مرحلة المنافسة. خلصت هذه الدراسة الى توضيح دور المسير في تفعيل الابتكار واستثمار المورد البشري باعتباره المورد الحساس والأكثر اهمية في المؤسسة, بالإضافة الى القيود العائلية و تأثيرها على قرارات المسير وبناء الخطط التكتيكية, في ظل غياب التخطيط الاستراتيجي للمؤسسات الصغيرة والمتوسطة الجزائرية بالرغم من وجود طاقات مبدعة, التي يمكن ان تثمر جهودها على المدى الطويل, والتي يمكن ان تدعم عن طريق البناء الاستراتيجي المستمر. The Small and medium enterprises have become playing an important aspect today in developed and developing countries economies alike .The managers of Small and medium enterprises should be aware that competitive edge depends mainly on innovation, whether at the local or global level because it is the most important factor in the transformation of the protection stage to the competition stage. This study concluded to clarify the role of an admin in activating the innovation and investment of human resource which is considered as the most important and sensitive one in the enterprise . In addition the family constraints and their impact on the decisions of the admin to give a tactical plans .Also the absence of strategic planning for the Algerian small and medium enterprises, despite there are much creative energies, which may give good results in the long term, which can be supported by continued strategic construction.
أطروحة مقدمة لنيل شهادة الدكتوراه في العلوم الاقتصادية
Keywords: ابتكار, مؤسسات الصغيرة والمتوسطة, مسير, ابداع, مورد بشري, تغيير في المؤسسة; Innovation, small and medium enterprises, admin , creativity, human resource, change in the enterprise